The use of photobioreactors in façades for decarbonization process - Marcos Antonio Leite Frandoloso; Sidnei Matana Júnior; Rodrigo Carlos Fritsch; Alan Rempel; Luciane Maria Colla; Eduardo Grala da Cunha; Júlia Medeiros Nicolodi; João Gabriel Cendron; Fábio Lamaison Pinto (Discover Sustainability)
Abstract The paper deals with the application of microalgae in building’s façade, regard to the broader project comprising the aspects of the environmental comfort of academic spaces and the energy consumption with on-grid photovoltaic generation, as well as the investigation of alternatives for the improvement of the performance of the building envelopes. Thus, its main objective is the application of interdisciplinary concepts involving Architecture and Biotechnology, as known by Black Ecologies, referring to an investigative interest to explore a new approach of nature, not only related to architectural space, but an emergent environmental focus. This relationship is performed by using photobioreactors with microalgae, installed on the façades of buildings for educational use. The present work presents the methodological outline of the research, based on literature review and case studies; complementary experimental methodologies are also presented to contextualize the subject and its application and feasibility. The current state of art showed an emergent approach in terms of international level, but in the Brazilian context any further research was identified yet. In addition to thermal and energy performance, the strategies will allow the process of sequestration of carbon dioxide and other GHG (greenhouse gases) that impacts on the process of climate change and can contribute to reach the sustainable development. This subject coincides with the discussions of the 2050 scenarios and emission reduction, which were faced at the recent COP-27 and its connections with an integrative way to contribute to the United Nations Sustainable Development Goals.